Posthypertonic Lysis of Red Blood Cells When Changing pH and Composition of Rehydrating Medium - Olejnic, O. A.; Ramazanov, V. V.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2002)
We have investigated the effect of rehydration medium composition on cells’ sensitivity to posthypertonic lysis. It has been shown that hypertonic rehydration media prevent red cell damages. Dilution of these media results in an increase of the hemolysis level. Application of PEG-1500 cryoprotectant allows to increase the cell integrity.